Parallels between astronauts and terrestrial patients – Taking physiotherapy rehabilitation "To infinity and beyond". (January 2017) - Hides, Julie; Lambrecht, Gunda; Ramdharry, Gita; Cusack, Rebecca; Bloomberg, Jacob; Stokes, Maria
Abstract: Exposure to the microgravity environment induces physiological changes in the cardiovascular, musculoskeletal and sensorimotor systems in healthy astronauts. As space agencies prepare for extended duration missions, it is difficult to predict the extent of the effects that prolonged exposure to microgravity will have on astronauts. Prolonged bed rest is a model used by space agencies to simulate the effects of spaceflight on the human body, and bed rest studies have provided some insights into the effects of immobilisation and inactivity. Whilst microgravity exposure is confined to a relatively small population, on return to Earth, the physiological changes seen in astronauts parallel many changes routinely seen by physiotherapists on Earth in people with low back pain (LBP), muscle wasting diseases, exposure to prolonged bed rest, elite athletes and critically ill patients in intensive care. The medical operations team at the European Space Agency are currently involved in preparing astronauts for spaceflight, advising on exercises whilst astronauts are on the International Space Station, and reconditioning astronauts following their return. There are a number of parallels between this role and contemporary roles performed by physiotherapists working with elite athletes and muscle wasting conditions. This clinical commentary will draw parallels between changes which occur to the neuromuscular system in the absence of gravity and conditions which occur on Earth. Implications for physiotherapy management of astronauts and terrestrial patients will be discussed. Highlights: Neuro-musculoskeletal changes in astronauts parallel changes in patients on Earth. Motor control training for low back pain patients is applicable to astronauts. Astronaut reconditioning principles may be relevant to intensive care patients. Benefits of exchanging physiotherapy practices between space and Earth are reciprocal.